Hydrodynamics of interceptor on planing boats - Mansoori, Mehran (UFRJ, 2015)
[PT] No presente trabalho são investigados os efeitos hidrodinâmicos do interceptor em navios de alta velocidade para encontrar as suas características geométricas ideais, mediante métodos numéricos e testes experimentais. O interceptor é uma placa vertical instalada simetricamente na popa do navio, que causa alterações na pressão de ruptura em torno do navio e especialmente no campo de pressões no final do casco. A variação de pressão tem efeitos sobre do calado e as forças de sustentação o que resulta em um melhor controle do trim. A altura do interceptor tem um efeito relevante na sua eficiência e deveria ser selecionada de acordo com a velocidade do navio e a espessura da camada limite. Com base nos resultados obtidos, pode-se afirmar que o interceptor não só diminui a intensidade da instabilidade do porpoising, mas também, pode controlar o fenômeno completamente. Além disso, os resultados mostraram que a combinação do interceptor com o trim tab apresenta uma melhoria notável no controle do trim, assim como, uma redução eficiente da resistência comparada com o interceptor ou trim tab independente.[EN] In this thesis, the effects of hydrodynamic interceptors on fast vessels are investigated to find their optimum geometrical characteristics based on numerical and experimental methods. Interceptors are vertical blades installed symmetrically at the aft of the craft and have been introduced as a new trim control device. They cause changes in pressure disruption around the vessel and especially at the end of the hull. The pressure variations have an effect on draft and lifting forces. The results show that the interceptor causes an intense pressure rate in its contact point. It also decreases the wet surface of the vessel and drag forces coefficient. At last, they lead to a better control of trim. The height of interceptor has an important effect and it should be selected according to the speed of the vessel and boundary layer thickness at the stern. The interceptor can completely control the porpoising phenomenon. Also the results show that, the combination of an interceptor and a trim tab shows remarkably better trim control and resistance reduction efficiency compared to an interceptor or a trim tab. Essentially the thesis contributes to the understanding of this new hydrodynamic device by devising the main parameters. It goes deeper showing that its application can be broad such as lowering resistance, with less trim and avoiding porpoising. The author is pretty confident that interceptors can become a standard device for fast speed vessels.